Análise da institucionalização do comitê de ética em pesquisa daUniversidade Federal de Minas Gerais (1997-2007): complexidades e desafios - Marcia dos Santos Pereira (2007)
In the twenty-first century, especially in poor countries, the social impacts of the rapid scientific development signalize for the need to broaden the debate on one of the pillars of bioethics: the issue of ethics in research in humans. Extremely consistent with this discussion, in Brazil, the resolution 196/1996 increases in a significant way the numberof Institutional Research Ethics Committees (RECs). Throughout the country, until May 2007, 546 RECs were registered linked to the National Commission for Research Ethics (CONEP). About the functioning of the RECs in Brazil, Freitas (2006, p. 51) notes: There is no a bibliography wide enough to bring a clear vision of reality, especially considering the diversity of experiences. Thus, the overall purpose of this thesis was tounderstand the phenomenon of institutionalization of the Committee on Ethics in Research at the Minas Gerais Federal University (COEP/UFMG) in the period of 1997- 2007. In this qualitative case study, based on knowledge of the called sciences of complexity, with data collected through observations and semi-structured interviews with 19 members of COEP, the information was analyzed, primarily from key conceptsof the institutional analysis, such as the instituted, instituting, the fact analyzer and social imagination. The institutional analysis, a search practice linked to the searchaction, to bring up the social interactions and relationships between the founding acts and the current issues of COEP/UFMG, was fundamental to the understanding of theprocess of institutionalization of the committee in its active and dynamic state and indicated that the great challenge today for the COEP/UFMG is to move beyond its bylaws, the acquisition of the budget and its own physical area, conditions of the resolution 196/1996 and obviously necessary, but not sufficient for the real exercise of its function to protect the research volunteers. Among other considerations, thediscourse analysis showed that members of COEP/UFMG is one interdisciplinary collegiate, independent of public interest, which has stimulated the debate on ethics in research in humans in that University. However, for them, not all of that University researchers have a clear vision of the tasks of this committee and believe that the weight of standardization and bureaucracy may be negatively influencing the process of institutionalization of COEP/UFMG and, in this respect, suggest that this committee needs to improve its relationship with the researchers, revise its protocols, streamline their work processes, monitor the projects approved and expand its educationalfunction. In this reflection, autonomy emerges as key issue of ethics in research in humans. Not the "individualistic autonomy" as highlighted at the present times, but the autonomy that emancipates, assumption necessary to speak on ethics, or the ability that people have to self determinate depending on the actual implementation and to sustain the struggle for social transformation, the ethics of the defense of life andhuman dignity. Thus, there is no mention of a moral ethics, but the idea of ethical implication of autonomous people, represented here by volunteers, by researchers and by the COEP/UFMG.